Feasibility, Visual Outcomes and Severity-Stratified Response to Pre-operative Intravitreal Bevacizumab Before Vitrectomy in Proliferative Diabetic Retinopathy - Ramzi Amin; Fajar Prasetya; Abdul Karim Ansyori (HM Publisher, 2026)
Background: Proliferative diabetic retinopathy is a leading cause of vision loss in working-age Indonesians, and pre-operative anti-vascular endothelial growth factor therapy has been proposed to make vitrectomy safer, yet Southeast Asian trial evidence is almost absent. Objective: To assess the feasibility, visual outcomes, and severity-stratified response to pre-operative intravitreal bevacizumab before 23-gauge pars plana vitrectomy in patients with proliferative diabetic retinopathy. Methods: In a single-centre, single-blind pilot randomised controlled trial at the Department of Ophthalmology, Faculty of Medicine, Universitas Sriwijaya/ Dr. Mohammad Hoesin Central General Hospital, Palembang (July–November 2025), 21 adults with proliferative diabetic retinopathy and non-clearing vitreous haemorrhage were allocated 1:1, stratified by haemorrhage severity, to intravitreal bevacizumab 1.25 mg/0.05 mL given 3–7 days before 23-gauge pars plana vitrectomy (n = 11) or to vitrectomy alone (n = 10). Progression criteria were pre-specified; the clinical outcome was best-corrected visual acuity change in LogMAR at one week. Results: All progression criteria fell in the green zone (recruitment 95.5%, 95% CI 78.2–99.2; retention and adherence 100%). Bevacizumab-treated eyes gained more vision, but imprecisely (Hodges–Lehmann shift 0.35 LogMAR, envelope 0.10 to 0.50; Hedges' g 0.65), the trial retaining only 14.8% power for the observed difference. Baseline vitreous haemorrhage severity dominated visual gain (adjusted B -0.397 LogMAR per grade, 95% CI -0.639 to -0.155; Cochran–Armitage trend p = 0.015). Conclusion: Pre-operative bevacizumab is feasible in an Indonesian tertiary centre and warrants a severity-stratified multicentre trial.